Sustained release of anticancer agent phytic acid from its chitosan-coated magnetic nanoparticles for drug delivery system - Barahuie, Farahnaz; Dorniani, Dena; Saifullah, Bullo; Gothai, Sivapragasam; Hussein, Mohd Zobir; Pandurangan, Ashok Kumar; Arulselvan, Palanisamy; Norhaizan, Mohd Esa (Dove Medical Press, 2017)
Chitosan (CS) iron oxide magnetic nanoparticles (MNPs) were coated with phytic acid (PTA) to form phytic acid-chitosan-iron oxide nanocomposite (PTA-CS-MNP). The obtained nanocomposite and nanocarrier were characterized by powder X-ray diffraction, Fourier transform infrared spectroscopy, vibrating sample magnetometry, transmission electron microscopy, and thermogravimetric and differential thermogravimetric analyses. Fourier transform infrared spectra and thermal analysis of MNPs and PTA-CS-MNP nanocomposite confirmed the binding of CS on the surface of MNPs and the loading of PTA in the PTA-CS-MNP nanocomposite. The coating process enhanced the thermal stability of the anticancer nanocomposite obtained. X-ray diffraction results showed that the MNPs and PTA-CS-MNP nanocomposite are pure magnetite. Drug loading was estimated using ultraviolet-visible spectroscopy and showing a 12.9% in the designed nanocomposite. Magnetization curves demonstrated that the synthesized MNPs and nanocomposite were superparamagnetic with saturation magnetizations of 53.25 emu/g and 42.15 emu/g, respectively. The release study showed that around 86% and 93% of PTA from PTA-CS-MNP nanocomposite could be released within 127 and 56 hours by a phosphate buffer solution at pH 7.4 and 4.8, respectively, in a sustained manner and governed by pseudo-second order kinetic model. The cytotoxicity of the compounds on HT-29 colon cancer cells was evaluated by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay. The HT-29 cell line was more sensitive against PTA-CS-MNP nanocomposite than PTA alone. No cytotoxic effect was observed on normal cells (3T3 fibroblast cells). This result indicates that PTA-CS-MNP nanocomposite can inhibit the proliferation of colon cancer cells without causing any harm to normal cell.